EFEKTIFITAS PENGGELOLAAN WAKAF PRODUKTIF BAGI KESEJAHTERAAN SOSIAL DI INDONESIA - Yasniwati, Yasniwati (UNES Law Review, 2023)
Currently, waqf is no longer identified with land that is given to educational institutions, cemeteries, places of worship or other things, but waqf can also be used as a source of strength for the welfare of the people and drives sectors of economic empowerment. The larger and more diverse waqf assets that can be managed professionally with proper management, the benefits derived from waqf management will be wider in designation so as to strengthen the role of waqf in improving the economy and welfare.